Pemenuhan Kebutuhan Pendidikan Kesehatan terhadap Kepatuhan Minum Obat pada Pasien Tuberculosis Paru di Rumah Sakit Putri Hijau Medan - Deni Susyanti; Syaiful Syaiful; Ratih Krisna Murti; Muchti Yuda Pratama (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
Pulmonary tuberculosis is a disease caused by Mycobacterium Tuberculosis bacteria which attacks a person’s respiratory system. This disease can spread through the air when an infected person coughing or sneezing secretes the droplet or saliva splash. These are what can cause a contagious infection adherence in pulmonary tuberculosis will cause the patient become MDR-TB. The health education provided to the pulmonary tuberculosis patient to increase their knowledge. This research used descriptive case study method, including Assessment, Diagnosis, Intervention, Implementation an Evaluation at 2 Pulmonary Tuberculosis patient at Putri Hijau Hospital. The research found that both pulmonary tuberculosis patient have different result after treated by health education treatment for 4 days, the first patient could overcome the lack of medication adherence while the second patient only could overcome certain of it.